A quantitative fecal examination for fascioliasis in ruminants on several farms of Rio Grande do Sul, Brazil - Girão, Eneide Santiago; Ueno, Hakaru (Pesquisa Agropecuaria Brasileira, 2014)
The quantitative fecal examination for fascioliasis in the ruminants of Rio Grande do Sul, Brazil, was carried out and evaluated employing a four-layer sieve technique (Girão 1982) in comparison with the original Dennis et al. technique (1954).One hundred and fifty-eight bovine and one hundred and sixty-four ovine fecal samples were collected in five counties of Rio Grande do Sul where fascioliasis of ruminants is a problem. The percentages of cattle and sheep fecal samples in which eggs of Fasciola hepatica were found by means of the four-layer sieve technique developed by Girão (1982) and by the original Dennis et al. technique (1954) were 45,6% and 43,7% in the cattle, and 61,6% and 57,9% in the sheep, respectively. No significant difference was observed (P < 0,05) in the number of the detection rate of F. hepatica eggs. The mean value of e.p.g. in bovine feces was 10.3 by the present technique and 11.2 with Dennis et al. technique (1954). However, in ovine fecal samples, e.p.g. was 41.6, but 30,9 with the Dennis et al. technique (1954).